Usefulness of “Nelaton Attachment” for endoscopic submucosal dissection of colorectal neoplasms - Yoshimoto, Taiji (Endosc Int Open, 2019)
Background and study aims  Although colorectal endoscopic submucosal dissection (ESD) has enabled high en bloc resection rates regardless of tumor size, colorectal ESD is still a challenging procedure. We developed a novel device called the Nelaton Attachment, which allows endoscopists to manipulate the ESD knives using two fingers of their left hand while holding the endoscope with their right hand. We retrospectively investigated the efficacy and safety of the Nelaton Attachment for colorectal ESD. We compared efficacy and safety between Nelaton Attachment and non-Nelaton Attachment groups, and also conducted an ex vivo experiment to evaluate the effect of the Nelaton Attachment. Patients and methods  We retrospectively reviewed 36 consecutive patients with 37 colorectal tumors who had undergone ESD at Kishiwada Tokushukai Hospital and Naritatomisato Tokushukai Hospital between April 2016 and September 2018. The Nelaton Attachment was used for 22 of the 37 colorectal ESDs. In the ex vivo experiment, endoscopists inserted and withdrew an ESD knife 2 cm using two fingers of their left hand with and without the Nelaton Attachment. Results  Median procedure time was significantly shorter in the Nelaton Attachment group (38 min [range 6 – 195 min]) compared to the non-Nelaton Attachment group (75 min [range 17 – 198 min]; P  = 0.030). Median time to complete the ex vivo experiment five times was significantly faster with the Nelaton Attachment than without the Nelaton Attachment ( P  = 0.001). Conclusions  Use of the Nelaton Attachment for colorectal ESD is feasible and safe, and may facilitate colorectal ESD procedures.